Analisis Pengaruh Kebijakan Kampus Bebas Asap Rokok Terhadap Persepsi Mahasiswa - Munissaniyah, Addina Firli; Nisa, Ulfatun; Fi Ilma, Mutiara; Samudoyo, Widadyo Bagus; Ningsih, Fathul Vidya; Nugraha, Joko Tri (FIA Unkris Press, 2026)
This research was conducted to analyze the link between the implementation of the Smoke-Free Campus (KBAR) policy and student perceptions within the university environment. The primary focus is to evaluate how effectively regulations and socialization efforts create a healthy, comfortable, productive academic atmosphere. By understanding student perspectives, institutions can accurately measure the success of such policies in supporting the creation of a high-quality and sustainable education sector. The study employs an associative quantitative design with descriptive approach. Primary data was gathered from 91 student respondents using questionnaires that passed rigorous validity and reliability testing. Data analysis was performed in depth using simple linear regression techniques to determine the specific influence between the variables involved. The research results revealed several significant findings. First, the KBAR policy has positive and significant impact on student perceptions, evidenced by a regression coefficient of 0.602. Second, based on determination analysis, this policy contributes 74.3% to shaping student perceptions, while the remaining 25.7% is influenced by external factors outside this study. The majority of students expressed high appreciation, as the policy effectively creates a cleaner learning environment and protects passive smokers from health risks. Crucial factors for KBAR’s effectiveness include intensive outreach through prohibitory signs and regular monitoring to increase collective awareness. In conclusion, consistent policy implementation by institutions is directly proportional to increasing student support. Success depends not only on written rules but on a genuine commitment to enforcing discipline for healthy campus.